Evaluation of Thermal Insulation of the Gastronomic Refrigeration Furniture Prototype (Agricultural Engineering, 2021)
An innovative method of insulation by injection to a cooling tank was investigated with consideration of a sustainable development need during production of thermo-insulation materials. An insulation material consisted of polyurethane foam. The manufacturer has chosen HFO gases for filling in the pores, since this is a product with a low environmental impact. HFO gases have a zero potential for destruction of the ozone layer and an extremely low global warming potential. Cooling tanks insulated with modern technologies of injection of polyurethane foam were investigated with regard to heat permission. They were also tested on account of occurrence of heat leakage bridges. The investigation covered also cooling furniture insulated with a conventional method of gluing ready-made polyurethane boards. The tests showed that a modern insulation technology influences reduction of the heat permission coefficient towards the presently applied technology. The investigated insulation of cooling furniture did not prove any heat leakage bridges. Therefore, it may be concluded that the technological process is correct. Cooling tanks manufactured in the present insulation technology did not show the occurrence of heat leakage bridges.